Structure and deduced function of the granaticin-producing polyketide synthase gene cluster of Streptomyces violaceoruber Tü22. - Sherman, D H (1989)
A 6.5 kb region of DNA from Streptomyces violaceoruber, which contains polyketide synthase (PKS) genes for production of the benzoisochromane quinone moiety of the antibiotic, granaticin, was cloned and sequenced. Of six open reading frames (ORFs) identified, four (ORFs 1-4) would be transcribed in one direction and two (ORFs 5 and 6) divergently from ORFs 1-4. ORF1 and ORF2, which show evidence for translation coupling, encode (deduced) gene products which strongly resemble each other and the Escherichia coli fatty acid ketoacyl synthase (condensing enzyme), FabB. We conclude that ORF1 (which contains a characteristic cysteine residue) functions as a condensing enzyme, possibly as part of a heterodimeric protein including the product of ORF2. The predicted ORF3 gene product strikingly resembles acyl carrier proteins (ACPs) of fatty acid synthase (FAS), particularly in the region of the active site motif, while the predicted ORF5 and ORF6 gene products resemble known oxidoreductases, suggesting that they function as reductive steps required during assembly of the granaticin carbon skeleton. Comparison of the deduced ORF4 gene product with available protein databases failed to elucidate its potential function. The overall conclusion is that the granaticin-producing PKS would consist of at least six separate enzymes involved in carbon chain assembly, thus resembling a Type II, rather than a Type I, FAS.